Soils of the Jurassic formations in the central Algarve; their occurrence, distribution, genesis and site qualities - Jahn, R. (2010)
In the central Algarve different soils have developed dependent on petrography of the parent material, slope position and recent erosion. The general patterns of occurence and distribution of different soils are described. The age of an eutric Nitosol is estimated and the relation between the soil and the parent material is investigated. Some different soils are described as examples with their chemical and physical properties. The water budget of soils is described in general with considerations concerning ground water recharge and run-off as well as in dependence of climate and of different site conditions.